IMPLEMENTATION OF CASHLESS POLICY STRATEGIES TO MINIMIZE FRAUD IN THE GOVERNMENT SECTOR: SYSTEMIC REVIEW - Ridwan Ridwan; Syukriy Abdullah; Fifi Yusmita (Jurnal Akuntansi, 2022)
Cashless financial transactions require information technology to transfer funds for the payment of needs, expenditures, and local government revenues. The potential that causes fraud and corruption can be minimized with non-cash transactions because financial transactions are more transparent. This study aims to identify fraud prevention strategies by implementing a cashless policy. This research was conducted systematically through an article search engine using the keywords "Casslhless" and "Fraud," which was then entered into the Scopus journal search engine based on secondary data in the publish or perish application 8. Then, journals and articles were selected based on the title theme and looked at the quality of the article. The result of this study is that local government payment system innovations have led to changes in payment options by switching to non-cash transactions that are safer, more effective, and efficient. Cashless payments can prevent corrupt practices such as money laundering, bribery, and commissions for services or procurement. People will use non-cash transactions if the local government forces non-cash payments in urban and rural areas with the support of the internet and promising technology. Local governments must report further non-cash payments and prioritize non-cash payments and make policies and innovations such as payment of social assistance to the community using digital money and payment of retribution using non-cash to increase local revenue.Keywords: Cashless, Corruption, Fraud.